Studies on electrolytic and doping behavior of different compounds and their combination on the electrical resistance of polypyrrole film via electrochemical polymerization. Issue 33 (11th July 2022) - Shukla, Ankur; Sen, Kushal; Das, Dipayan
Abstract: Electrochemical polymerization of pyrrole requires a supporting compound for higher polymer yield. Such compounds have been designated as electrolyte or as dopant. This article examines the roles of such compounds when used individually or in combination for the synthesis of polypyrrole films and polypyrrole coated polyester fabric via in situ electrochemical polymerization. With a view to obtain higher polymer deposition, the effect of 0.15 mM concentration of sodium nitrate, sodium anthraquinone‐2‐sulfonate, p‐toluenesulfonic acid and oxalic acid on the system current and the surface resistance was examined by means of chronoamperometry technique. FTIR and WAXD spectra were used to establish the formation of polypyrrole and doping of different compounds. SEM analysis confirmed deposition of polypyrrole onto the fabric. The charge utilization factor helped in identifying a good dopant. Sulfonic acid‐based salt AQSA‐Na was found to be useful as a dopant as well as an electrolyte. A combination of 0.075 mM sodium nitrate as an electrolyte and 0.075 mM pTSA as a dopant resulted in least surface resistance of polypyrrole film and polypyrrole coated polyester fabric which was almost 88% lower than the polypyrrole coated polyester fabric prepared using the surface resistance of polypyrrole coated polyester fabric via pyrrole vapor polymerization. Abstract :